1980
DOI: 10.1128/jvi.36.3.766-774.1980
|View full text |Cite
|
Sign up to set email alerts
|

Abelson murine leukemia virus mutants deficient in kinase activity and lymphoid cell transformation

Abstract: Abelson murine leukemia virus transforms both lymphoid cells and fibroblasts in vitro and induces a unique type of thymus-dependent lymphoma in vivo. Four fibroblast-transforming strains of Abelson murine leukemia virus were identified, based on the sizes of the Abelson murine leukemia virus-specific phosphoproteins produced by these isolates. Two of these strains, the standard P120and the P160-producing viruses, transformed lymphoid cells efficiently in vitro and induced Abelson disease in vivo. Two other str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 23 publications
1
60
0
Order By: Relevance
“…Subcutaneous tumors at the site of injection were common in the former two cases. The second is that the time course of tumor appearance in the mice injected with the P90-infected cells was similar to that found upon injection of mice with P90 virus preparations (22). We are presently examining the frequency of tumors that arise which are of host or donor origin by using F1 mice as recipients of the P90and P160-infected BALB/c lymphocytes.…”
Section: A~~~~~~~~~~~~~~pmentioning
confidence: 65%
See 3 more Smart Citations
“…Subcutaneous tumors at the site of injection were common in the former two cases. The second is that the time course of tumor appearance in the mice injected with the P90-infected cells was similar to that found upon injection of mice with P90 virus preparations (22). We are presently examining the frequency of tumors that arise which are of host or donor origin by using F1 mice as recipients of the P90and P160-infected BALB/c lymphocytes.…”
Section: A~~~~~~~~~~~~~~pmentioning
confidence: 65%
“…Increased efficiency of target cell growth of bone marrow cells infected by the P90 strain of A-MuLV. Although the P90 strain of A-MuLV is capable of transforming NIH-3T3 fibroblasts with a high efficiency, bone marrow cells infected with P90 show a 10to 30-foldlower frequency of agar colony transformation with P120 and P160 (22). A lower efficiency of bone marrow transformation with P90 was also observed in liquid cultures, a large fraction of which failed to show detectable growth of target cells even after 17 days of culture (22).…”
Section: A~~~~~~~~~~~~~~pmentioning
confidence: 95%
See 2 more Smart Citations
“…Normal c-Abl is unable to transform cells, even if overexpressed (Jackson and Baltimore, 1989), but can be activated to transform fibroblasts and hematopoietic cells by several distinct mechanisms, including deletions (Franz et al, 1989;Jackson and Baltimore, 1989) or point mutations (Van Etten et al, 1995) in the SH3 domain, substitution of polypeptides derived from retroviral gag (Van Etten et al, 1995), BCR (Shtivelman et al, 1985;Stam et al, 1985) or TEL (Papadopoulos et al, 1995) genes at the extreme N-terminus, and point mutations in the kinase domain (Jackson et al, 1993b). Fibroblast transformation by activated Abl requires tyrosine kinase activity (Rosenberg et al, 1980;Engelman and Rosenberg, 1987;Kipreos et al, 1987), the phosphotyrosine binding function of the SH2 domain (Mayer et al, 1992) and myristoylation (Daley et al, 1992). The functions of the c-ras (Smith et al, 1986;Stacey et al, 1991;Sawyers et al, 1995) and c-myc (Sawyers et al, 1992) genes are required for Abl transformation, and activated Abl has been identified recently as a potent stimulator of the stress-activated protein kinase pathway (Sanchez et al, 1994).…”
Section: Introductionmentioning
confidence: 99%